"I'm Going to Israel and All I Need to Pack Is My Imagination": Pretend Trips to Israel in Jewish Early Childhood Education. Issue 1 (2nd January 2020) - Applebaum, Lauren; Zakai, Sivan
ABSTRACT: This article examines the practice of pretend Israel trips in Jewish early childhood education. Jewish early childhood educators who work in markedly different preschool settings, and who have differing beliefs about Israel and Israel education, nonetheless converge on a practice of pretend trips to Israel that remains remarkably stable across settings. This article examines how and why these pretend trips have become part of the "grammar" of Jewish early childhood education, illuminating a practice that is simultaneously beloved and unsatisfying for Jewish early childhood educators who care about early childhood education and Israel education.